Glass - Hopkins, Ellen (New York : Simon & Schuster, 2007)
Kristina thinks she can control it. With a baby to care for, she's determined to decide when and how much, to be the one calling the shots. But the monster is too strong, and before she knows it, Kristina is back in its grips. She needs the monster to keep going, to face the pressures of day-to-day life. She needs it to feel alive.
Sequel to Crank.
Keywords: Drug abuse -- Juvenile fiction; Teenagers -- Drug use -- Juvenile fiction; Teenagers -- Substance use -- Juvenile fiction; Ice (Drug) -- Juvenile fiction; Novels in verse